Candidate genes for hereditary colorectal cancer: Mutational screening and systematic review. Issue 9 (28th July 2020) - Belhadj, Sami; Terradas, Mariona; Munoz‐Torres, Pau M.; Aiza, Gemma; Navarro, Matilde; Capellá, Gabriel; Valle, Laura
Abstract: Genome‐wide approaches applied for the identification of new hereditary colorectal cancer (CRC) genes, identified several potential causal genes, including RPS20, IL12RB1, LIMK2, POLE2, MRE11, POT1, FAN1, WIF1, HNRNPA0, SEMA4A, FOCAD, PTPN12, LRP6, POLQ, BLM, MCM9, and the epigenetic inactivation of PTPRJ . Here we attempted to validate the association between variants in these genes and nonpolyposis CRC by performing a mutational screening of the genes and PTPRJ promoter methylation analysis in 473 familial/early‐onset CRC cases, a systematic review of the published cases, and assessment of allele frequencies in control population. In the studied cohort, 24 (5%) carriers of (predicted) deleterious variants in the studied genes and no constitutional PTPRJ epimutations were identified. Assessment of allele frequencies in controls compared with familial/early‐onset patients with CRC showed association with increased nonpolyposis CRC risk of disruptive variants in RPS20, IL12RB1, POLE2, MRE11 and POT1, and of FAN1 c.149T>G (p.Met50Arg). Lack of association was demonstrated for LIMK2, PTPN12, LRP6, PTPRJ, POLQ, BLM, MCM9 and FOCAD variants. Additional studies are required to provide conclusive evidence for SEMA4A, WIF1, HNRNPA0 c.−110G>C, and FOCAD large deletions. Abstract : We performed a mutational screening of 17 recently reported candidate genes for CRC predisposition in a cohort of 473 familial/early‐onset CRC patients. The available literature for each candidate gene was thoroughly reviewed and the reported variants were reclassified and combined with our results in a gene‐centered meta‐analysis. Enrichment of disruptive variants in CRC cases compared with population controls was detected in five of the 17 genes: RPS20, IL12RB1, POLE2, MRE11 and POT1 .